Synthesis & Characterization of Chitosan Schiff Base Hydrogel for Controlled Drug Release - Maha A. Younus (Journal of Global Pharma Technology, 2019)
Chitosan-schiff base with three different ratios of para-Dimethyl aminobenzaldehyde& chitosan Schiff base hydrogels have been prepared for controlled drug release study. The synthesized chitosan Schiff base and chitosan Schiff base hydrogel were characterized by FT-IR, UV-Visible, SEM, analysis. Swelling properties of the hydrogel were investigated at three different media pH (2, 7, 10). The swelling degree varied with the pH, amount of crosslinking agent glutaraldehyde and with the amount of para-Dimethylaminobenzaldehyde for the hydrogels. All hydrogels were used for controlled drug release system. Aspirin was used as model drug, in three different buffer solution (2, 7, 10) as release media. The rate of release of drugs in the pH2 is more than that of pH7 and pH10 in the polymer hydrogels.Keywords: Chitosan, Chitosan Schiff base, Hydrogel, Controlled drug release.